Causal relationship between anti-inflammatory drugs and cancer: a pan-cancer study with Mendelian randomization - Gao, Shen; Wei, Guojiang; Ma, Qianwang; Wang, Xue; Wang, Sen; Niu, Yuanjie (Frontiers in Genetics, 2024)
Background: Numerous epidemiological studies have elucidated the intricate connection between inflammation and cancer, highlighting how sustained inflammatory responses can fuel carcinogenesis by fostering proliferation, angiogenesis, and metastasis, while dampening immune responses and sensitivity to chemotherapy. Previous clinical investigations have underscored the potential of antiinflammatory medications in either preventing or mitigating tumor formation. Here, the causal relationship between anti-inflammatory drugs and cancer was further explored through Mendelian randomization studies.Methods: Employing Mendelian randomization, we scrutinized the causal links between three anti-inflammatory drugs-NSAIDs, Aspirin, and Anilide-and 37 types of cancer. We primarily utilized inverse variance weighting (IVW) as the primary analytical approach to delineate the causal association between these drugs and cancer types. Concurrently, sensitivity analyses were conducted to ascertain the absence of horizontal pleiotropy and heterogeneity.Results: Our investigation revealed a discernible causal relationship between certain anti-inflammatory drugs and a subset of cancers, albeit without a pervasive impact across all cancer types. Specifically, NSAIDs exhibited a risk-reducing effect on nonsmall cell lung cancer (OR: 0.76, 95% CI: 0.59-0.97, P value: 0.03) and gastric cancer (OR: 0.57, 95% CI: 0.34-0.98, P value: 0.04). Conversely, aspirin was associated with an increased risk of oral malignant tumors (OR: 2.18, 95% CI: 1.13-4.21, P value: 0.02).Notably, no statistically significant findings were observed for anilide drugs (P < 0.05).We identified several cancers with potential causal links to NSAIDs, including non-small cell lung cancer and gastric cancer. Despite our extensive analysis, we did not identify a substantial causal relationship between the use of antiinflammatory drugs and the development of various cancers.